Analysis of the Completeness of Electronic Medical Records in Outpatient Installations to Improve the Quality of Service in Hospital - Nurlatifah , Any; Susanti, Ai Susi (Journal of Scientific Insights, 2025)
Digital transformation in the health sector encourages the adoption of Electronic Medical Records (EMR) as an effort to improve the quality of service and efficiency of information systems. This study aims to analyze the level of completeness of EMR filling in the Outpatient Installation of Hospital X and identify the factors that influence it. The method used is quantitative descriptive with data obtained from 100 outpatient EMR documents during March–April 2025. The results show that only the patient identity component reaches 100% completeness, while other components such as anamnesis, actions, and therapy are still low (52%), followed by CPPT (65%), doctor's signature (67%), physical examination (77%), and diagnosis (90%). This incompleteness risks reducing the quality of service, patient safety, and validity of documentation. The main factor contributing to incompleteness is limited human resources, especially elderly officers who have difficulty adapting to digital systems. The study recommends intervention strategies such as needs-based training, intergenerational mentoring, and routine evaluation to improve compliance with EMR filling. In conclusion, the success of RME implementation does not only depend on the digital system, but also on the readiness of human resources, documentation culture, and management support in building quality health services.